Effects of repeated bouts of squatting exercise on sub-maximal endurance running performance - Burt, D.; Lamb, K.; Nicholas, C.; Twist, C. (European Journal of Applied Physiology, 2013)
It is well established that exercise-induced muscle damage (EIMD) has a detrimental effect on endurance exercise performed in the days that follow. However, it is unknown whether such effects remain after a repeated bout of EIMD. Therefore, the purpose of this study was to examine the effects of repeated bouts of muscle-damaging exercise on sub-maximal running exercise. Nine male participants completed baseline measurements associated with a sub-maximal running bout at lactate turn point. These measurements were repeated 24-48 h after EIMD, comprising 100 squats (10 sets of 10 at 80 % body mass). Two weeks later, when symptoms from the first bout of EIMD had dissipated, all procedures performed at baseline were repeated. Results revealed significant increases in muscle soreness and creatine kinase activity and decreases in peak knee extensor torque and vertical jump performance at 24-48 h after the initial bout of EIMD. However, after the repeated bout, symptoms of EIMD were reduced from baseline at 24-48 h. Significant increases in oxygen uptake (VO2) , minute ventilation (VE) , blood lactate ([BLa]), rating of perceived exertion (RPE), stride frequency and decreases in stride length were observed during sub-maximal running at 24-48 h following the initial bout of EIMD. However, following the repeated bout of EIMD, VO2,VE, [BLa], RPE and stride pattern responses during sub-maximal running remained unchanged from baseline at all time points. These findings confirm that a single resistance session protects skeletal muscle against the detrimental effects of EIMD on sub-maximal running endurance exercise.